Quality of life in obese patients from a multidisciplinary bariatric consultation: a cross-sectional study comparing to a non-bariatric population and to the general population - Figueiredo, Inês Rego de (2022)
Obesity is a chronic disease defined by a body mass index of ≥30 kg/m2, which can result in a decrease in quality of life (QoL). Our study aim was to assess the QoL of an obese population of bariatric surgery (BS) candidates and to compare it to both that of a non-bariatric obese population (C) and that of the general population. This was a cross-sectional study using: (1) the EQ-5D-3L instrument: comparing BS with the C population and with the Portuguese general population; and (2) the Bariatric Quality of Life (BQL) Index: comparing the two groups of obese patients. We included 228 BS and 68 C obese patients. BS patients had higher BMI (44 ± 6 kg/m2 vs. 41 ± 6.5 kg/m2; p < 0.001), higher waist circumference (130 ± 13 cm vs. 123 ± 17 cm; p = 0.03), and higher total body fat mass (49.9 ± 6.7% vs. 45 ± 6.7%; p < 0.001). QoL as evaluated by EQ-5D-3L was similar, but the BQL index showed lower QoL in BS patients (40.9 ± 8.9 vs. 44.2 ± 11.2; p = 0.01). Compared to the Portuguese general population, BS patients had lower QoL (VAS: 55 ± 19 vs. 74.9; p < 0.001; index: 0.33 ± 0.2 vs. 0.76; p < 0.001). Despite higher adiposity in the BS group, QoL was similar between the groups by EQ-5D-3L. Nevertheless, there was a decrease in the QoL for the BS patients as determined using the BQL, a tool with higher sensitivity to bariatric patients.